Integrated GIS and AHP-Based Air Quality Zonation in the Kurdistan Region of Iraq - Chomani, Kaifi (Zanco Journal of Pure and Applied Sciences, 2025)
Kurdistan Region of Iraq (KRI) faced significant challenges related to air quality due to the rapid urbanization and industrial activities, which necessitate the air quality assessments. The advanced techniques of remote sensing, Geographic Information Systems (GIS), and the Analytic Hierarchy Process (AHP) were combined in this research to perform air quality zonation for the KRI. The Ozone (O3), Nitrogen Dioxide (NO2), Sulfur Dioxide (SO2), Carbon Monoxide (CO), and UV Aerosol Index, were the selected air pollutants from Sentinel 5P as average of 2024 to use as a critical parameters for air quality assessments. The considered parameters were weighted using pairwise comparison, and thematic maps were created to calculate air quality zonation map for KRI. The results were categorized into five pollution levels: very low, low, medium, high, and very high. The findings showed that 2,815 km² (6.1%) of KRI identified as region with very high air pollution, suggesting the critical need for targeted mitigation strategies. This study aid notably in sustainable environment and offers important information for policymakers to enhance public safety.